2009
DOI: 10.1534/genetics.109.104844
|View full text |Cite
|
Sign up to set email alerts
|

Conservation of Domain Structure in a Fast-Evolving Heterochromatic SUUR Protein in Drosophilids

Abstract: Different genomic regions replicate at a distinct time during S-phase. The SuUR mutation alters replication timing and the polytenization level of intercalary and pericentric heterochromatin in Drosophila melanogaster salivary gland polytene chromosomes. We analyzed SuUR in different insects, identified conserved regions in the protein, substituted conserved amino acid residues, and studied effects of the mutations on SUUR function. SuUR orthologs were identified in all sequenced drosophilids, and a highly div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 53 publications
(65 reference statements)
0
5
0
Order By: Relevance
“…Thus, the physical interaction between H1 and the central fragment of SUUR is direct. Importantly, an overlapping fragment of SUUR (361-599) has been shown previously to be required for the localization of SUUR to chromatin, including IH, in vivo (Kolesnikova et al 2005;Yurlova et al 2009). Therefore, the central region of SUUR, which encompasses a positively charged domain and the nuclear localization signal (NLS), is sufficient to mediate a strong physical interaction with H1 and may be involved in tethering SUUR to H1-containing chromatin in vivo.…”
Section: Suur and H1 Proteins Interact Physicallymentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the physical interaction between H1 and the central fragment of SUUR is direct. Importantly, an overlapping fragment of SUUR (361-599) has been shown previously to be required for the localization of SUUR to chromatin, including IH, in vivo (Kolesnikova et al 2005;Yurlova et al 2009). Therefore, the central region of SUUR, which encompasses a positively charged domain and the nuclear localization signal (NLS), is sufficient to mediate a strong physical interaction with H1 and may be involved in tethering SUUR to H1-containing chromatin in vivo.…”
Section: Suur and H1 Proteins Interact Physicallymentioning
confidence: 99%
“…We now demonstrate that the central region of SUUR is also sufficient for binding directly to H1 in vitro. Considering that the central region of SUUR is essential for the faithful localization of the protein to chromatin in vivo, including underreplicated IH (Kolesnikova et al 2005;Yurlova et al 2009), it seems likely that H1 directly mediates the tethering of SUUR to chromatin in underreplicated regions.…”
Section: Dissection Of the Physical Interaction Between H1 And Suurmentioning
confidence: 99%
“…11,13 It is worth mentioning that SuUR is a fast-evolving gene that was found only in Diptera. 16 Despite the low evolutionary conservation, recent studies revealed several important features of Figure 1. Replication and under-replication in polytene chromosome.…”
mentioning
confidence: 99%
“…16 However, it is unlikely that chromatindependent regulation of replication fork progression is a phenomenon restricted to Diptera. In mammals and other eukaryotes, SUUR function may well be performed by a different protein.…”
mentioning
confidence: 99%
“…15 Targeted mutation of two aminoacid residues in this domain renders the protein incapable of forming the swellings. 24 SWI2/SNF2 family ATP-binding domains normally play catalytic roles in a plethora of chromatin remodeling complexes. Such complexes can have specific genomic targets and mediate local structural changes in chromatin.…”
Section: Sgs3-gal4 Suurmentioning
confidence: 99%